Disease and disparities structural violence in the time of our covidized lives - Agcaoili, Aurelio S. (Budhi: a Journal of Ideas and Culture, 2020)
The paper argues that when a country's social structures - political, economic, and cultural - are arranged such that the arrangement results in a dichotomy between the class of the privileged, any act of addressing a pandemic such as the COVID-19 will always end up in another pandemic: the pandemic of government neglect and ineptitude. There is only one way out in ensuring that this double pandemic can be addressed: a return to the foundations of a good life for all - a democracy that secures that the good of collective life is for all.